1994
DOI: 10.1111/j.1365-3024.1994.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation of human alpha‐1–antitrypsin with components in Schistosoma mansoni cercariae

Abstract: Human alpha-1-antitrypsin (alpha 1-AT) was incubated with an extract of Schistosoma mansoni cercariae or porcine pancreatic elastase and analysed by immunoelectrophoresis and Western blotting. The inhibitor was shown to form complexes with components in S. mansoni cercariae in the same way as elastase. The role of alpha 1-AT in S. mansoni infection is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our finding is consistent with a previous report by Darani et al (1997) who showed the native elastase to be poorly immunogenic when injected into mice. Reasons for the apparently poor immunogenicity of the native enzyme may be a consequence of the enzyme's ability to degrade host immunoglobulins and complement (Auriault et al 1981; Marikovsky et al 1988; Darani et al 1997; Pleass et al 2000) or its interaction with serine protease inhibitors in the host (Mast et al 1991; Modha and Doenhoff, 1994 a , b ). The latter was found to result in rapid clearance of the enzyme from the circulation preventing its normal processing by the antigen-presenting cells (Mast et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is consistent with a previous report by Darani et al (1997) who showed the native elastase to be poorly immunogenic when injected into mice. Reasons for the apparently poor immunogenicity of the native enzyme may be a consequence of the enzyme's ability to degrade host immunoglobulins and complement (Auriault et al 1981; Marikovsky et al 1988; Darani et al 1997; Pleass et al 2000) or its interaction with serine protease inhibitors in the host (Mast et al 1991; Modha and Doenhoff, 1994 a , b ). The latter was found to result in rapid clearance of the enzyme from the circulation preventing its normal processing by the antigen-presenting cells (Mast et al .…”
Section: Discussionmentioning
confidence: 99%
“…The latter was found to result in rapid clearance of the enzyme from the circulation preventing its normal processing by the antigen-presenting cells (Mast et al . 1991; Modha and Doenhoff, 1994 a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that levels of IgE, IL-8 and A1AT rise dramatically after infection with helminth parasites 56 . Indeed A1AT is known to bind directly to schistosomes 57 , is upregulated in the livers of infected animals 58 , and infections with schistosomes aggravate liver disease 59 . Thus A1AT may protect IgE from the damaging effects of serine proteases derived from migrating parasites.…”
Section: Discussionmentioning
confidence: 99%